2020
DOI: 10.1111/gcb.15209
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting mechanisms underlie short‐ and longer‐term soil respiration responses to experimental warming in a dryland ecosystem

Abstract: Soil carbon losses to the atmosphere through soil respiration are expected to rise with ongoing temperature increases, but available evidence from mesic biomes suggests that such response disappears after a few years of experimental warming. However, there is lack of empirical basis for these temporal dynamics in soil respiration responses, and for the mechanisms underlying them, in drylands, which collectively form the largest biome on Earth and store 32% of the global soil organic carbon pool. We coupled dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 73 publications
(141 reference statements)
2
26
1
Order By: Relevance
“…δ 13 C in soil organic matter (SOM) is c. −26, while in atmospheric CO 2 it is c. −8; Lakatos et al, 2007). Increased soil respiration in biocrust-dominated soils has been reported during the first years of simulated warming and rainfall reduction (Maestre et al, 2013;Escolar et al, 2015;Dacal et al, 2020). However, it would then be expected that P. decipiens, characterized by discontinuous darker squamules (small, scale-like thallus units), should also have higher evaporation rates under these experimental conditions and, simultaneously, capture more water from nonliquid precipitation than more continuous species because of its higher surface area (Raggio et al, 2014).…”
Section: New Phytologistmentioning
confidence: 99%
See 1 more Smart Citation
“…δ 13 C in soil organic matter (SOM) is c. −26, while in atmospheric CO 2 it is c. −8; Lakatos et al, 2007). Increased soil respiration in biocrust-dominated soils has been reported during the first years of simulated warming and rainfall reduction (Maestre et al, 2013;Escolar et al, 2015;Dacal et al, 2020). However, it would then be expected that P. decipiens, characterized by discontinuous darker squamules (small, scale-like thallus units), should also have higher evaporation rates under these experimental conditions and, simultaneously, capture more water from nonliquid precipitation than more continuous species because of its higher surface area (Raggio et al, 2014).…”
Section: New Phytologistmentioning
confidence: 99%
“…total C and N) of both biocrust‐forming lichens and mosses is expected to be reduced with increased temperature and altered rainfall regimes as a result of reduced physiological performance (Reed et al ., 2012), as has been shown along climatic gradients in the field (Concostrina‐Zubiri et al ., 2018). Thus, lichens are expected to play an important role in modulating climate change effects on soil diversity and functioning (Maestre et al ., 2015; Liu et al ., 2016; Dacal et al ., 2020). Understanding how climate change will differentially impact dominant biocrust‐forming lichen species is critical to better forecasting how climate change will impact ecosystem functioning in drylands.…”
Section: Introductionmentioning
confidence: 99%
“…The first one (hereafter Experiment 1) in El Cautivo, where we assessed the sensitivity of lichen physiological processes and cover towards systematic changes in single and combined climate variables. The second experiment (hereafter Experiment 2) mimicked and extended an ongoing climate change experiment in Aranjuez (Dacal et al, 2020;Maestre et al, 2013) to determine the mechanisms leading to the observed changes in biocrust cover and to see how well the model can be transferred to other sites despite the intra-specific physiological variability of D. diacapsis (Lange et al, 1997;Pintado et al, 2005).…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…Considering the temporal and spatial scales at which climate change is operating, experiments and field studies have some major limitations. First, they are restricted to relatively small research areas and short time-scales: all experiments conducted to date have been running for 15 years or less (Dacal et al, 2020;Ferrenberg et al, 2015). Second, manipulative climate change treatments potentially introduce unintended side effects that can influence the results (Carlyle et al, 2011) and different manipulation methods can hamper the comparison between studies (Bokhorst et al, 2013;Klein et al, 2005;Ladrón de Guevara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To adequately explore the potential mechanisms shaping the responses of autotrophic and heterotrophic respiration to N input, we also evaluated the effects of other environmental (soil temperature, pH, etc. ; Dacal et al., 2020; Luo & Zhou, 2006), plant (gross primary productivity, root biomass, plant functional traits, etc. ; Bardgett et al., 2014) and microbial (soil total phospholipid fatty acids [PLFAs], extracellular enzyme activity, etc.…”
Section: Introductionmentioning
confidence: 99%